2018
DOI: 10.1111/1742-6723.12968
|View full text |Cite
|
Sign up to set email alerts
|

Medication use in infants admitted with bronchiolitis

Abstract: Medication was used for infants with bronchiolitis frequently and variably in Australia and New Zealand. Medication use increased with age. Better strategies for translating evidence into practice are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 43 publications
2
41
1
2
Order By: Relevance
“…Our rates of salbutamol use are lower than previous reports in the Australasian context but remain higher than expected given the strong recommendation. Although evidence in subgroups remains weak, the number needed to treat and lack of evidence for reduction in needing oxygen use or improvement in hospital length of stay has led to the strong recommendation not to use CXR in any subgroup.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…Our rates of salbutamol use are lower than previous reports in the Australasian context but remain higher than expected given the strong recommendation. Although evidence in subgroups remains weak, the number needed to treat and lack of evidence for reduction in needing oxygen use or improvement in hospital length of stay has led to the strong recommendation not to use CXR in any subgroup.…”
Section: Discussioncontrasting
confidence: 83%
“…12 An Australasian study showed rates of bronchodilator use in patients admitted to hospital with bronchiolitis varying from 27 to 48.7%, increasing with age. 13 Our institution is a major specialist paediatric hospital with over 85 000 emergency presentations per year and 50 000 inpatient episodes. We produce widely accessed, evidence-based clinical practice guidelines.…”
Section: What This Paper Addsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of Emergency Medicine Australasia , Oakley et al . report a retrospective review of a cohort of infants with bronchiolitis, examining the use of medications in the treatment of bronchiolitis.…”
Section: Competing Interestsmentioning
confidence: 99%
“…In this issue of Emergency Medicine Australasia, Oakley et al 1 report a retrospective review of a cohort of infants with bronchiolitis, examining the use of medications in the treatment of bronchiolitis. They demonstrate that despite high-quality evidence confirming medications are of no clinical benefit, almost half of the children with bronchiolitis receive at least one such medication during their treatment.…”
mentioning
confidence: 99%